the effectiveness of banking information systems, and their role in the management of non-performing loans - ameur, saloua; beladjouz, hocine (Journal of Research in Finance and Accounting, 2023)
Algerian commercial banks, and their role in the management of non-performing loans,in order to achieve the objectives of the study we designed a questionnaire And we distributed it to the employees of the National Bank of Algeria (BNA) -M'sila Agency- For this, the necessary data was collected the statistical package for social sciences) spss (was used to analyse and examine hypotheses, The study reached to several conclusions; the most important were:- Banking information systems in Algerian commercial banks, are effective in applying the requirements of planning, control and decision-making operations.-Effective banking information systems contribute significantly to the follow-up and management of non-performing loan According to the finding of the study list bellow shows in the most important recommendations: - Algerian banks must work to keep abreast of the various technological developments in the financial and accounting field in order to develop banking information systems - benefit from the methods and methods of dealing with non-performing loans from the experiences of other countries.